Trauma culture : the politics of terror and loss in media and literature - Kaplan, E. Ann. (Piscataway : Rutgers University Press, 2005)
It may be said that every trauma is two traumas or ten thousand-depending on the number of people involved. How one experiences and reacts to an event is unique and depends largely on one's direct or indirect positioning, personal psychic history, and individual memories. But equally important to the experience of trauma are the broader political and cultural contexts within which a catastrophe takes place and how it is "managed" by institutional forces, including the media. In Trauma Culture, E. Ann Kaplan explores the relationship between the impact of trauma on individuals.
Introduction : 9/11 and "disturbing remains" -- "Why trauma now?" : Freud and trauma studies -- Memory as testimony in World War II : Freud, Duras, and Kofman -- Melodrama and trauma : displacement in Hitchcock's Spellbound -- Vicarious trauma and "empty" empathy : media images of Rwanda and the Iraq War -- "Translating" trauma in postcolonial contexts : indigeneity on film -- The ethics of witnessing : Maya Deren and Tracey Moffatt -- Epilogue : "Wounded New York" : rebuilding and memorials to 9/11.
Print version record.
Includes bibliographical references and index.
English.
JSTOR
Keywords: Terrorism in motion pictures; Disaster films -- History and criticism; Psychic trauma in motion pictures; Psychic trauma in literature; Literature, Modern -- 20th century -- History and criticism; Culture in motion pictures; Films-catastrophes -- Histoire et critique; Traumatisme psychique au cinéma.; Traumatisme psychique dans la littérature.; Culture au cinéma.; Terrorisme au cinéma.; Littérature -- 20e siècle -- Histoire et critique; ART -- Film & Video; PERFORMING ARTS -- Film & Video -- Reference; SOCIAL SCIENCE -- Media Studies; Culture in motion pictures; Disaster films; Literature, Modern; Psychic trauma in literature; Psychic trauma in motion pictures; Terrorism in motion pictures; Film; Music, Dance, Drama & Film; 1900-1999; Criticism, interpretation, etc